2023
DOI: 10.3389/fonc.2023.1110689
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognostic factors in initially unresectable hepatocellular carcinoma treated using conversion therapy with lenvatinib and TACE plus PD-1 inhibitors

Abstract: PurposeTo evaluate the outcomes and prognostic factors for patients using conversion therapy with lenvatinib combined with transcatheter arterial chemoembolization (TACE) plus programmed cell death protein-1 (PD-1) inhibitors (LTP) for initially unresectable hepatocellular carcinoma (iuHCC).MethodsData on 94 consecutive patients with iuHCC who received LTP conversion therapy from November 2019 to September 2022 were retrospectively analyzed. Early tumor response was reported when patients showed complete or pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Additionally, these HCC patients may be cured only by conversion resection. TACE-based combination therapy is playing an increasingly important role in tumor downstaging and translational surgical resection of unresectable hepatocellular carcinoma because of its better tumor response rate and better survival benefit ( 29 ). Romic et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these HCC patients may be cured only by conversion resection. TACE-based combination therapy is playing an increasingly important role in tumor downstaging and translational surgical resection of unresectable hepatocellular carcinoma because of its better tumor response rate and better survival benefit ( 29 ). Romic et al.…”
Section: Discussionmentioning
confidence: 99%
“…based combination therapy is playing an increasingly important role in tumor downstaging and translational surgical resection of unresectable hepatocellular carcinoma because of its better tumor response rate and better survival benefit (29). Romic et al reported that this translational surgical resection resulted in better clinical outcomes and a better survival prognosis (30).…”
Section: Discussionmentioning
confidence: 99%
“…Another effective regimen might be TACE followed by hepatic arterial infusion chemotherapy, as reported by Li et al [ 15 ]. Moreover, in patients who successfully underwent conversion therapy, the subsequent surgical treatment appears to be associated with more prolonged survival compared to non-surgical management, albeit with possibly increased perioperative risk [ 16 , 17 , 18 , 19 ]. Finally, the new IMBRAVE trial has shown the effectiveness of adjuvant therapy for the first time in decreasing the risk of post-surgical tumor recurrence in high-risk HCC patients, which was confirmed in widespread reproducibility studies [ 20 , 21 , 22 , 23 , 24 ].…”
Section: Are There New Perspectives In Hcc Treatment?mentioning
confidence: 99%
“…Although participants' baseline characteristics and the definition of conversion to resectable HCC varied among studies, conversion rates were 25-50%, based on the good ORR performance of triple therapy (16)(17)(18)(19).…”
Section: Triple Therapy In Conversion Surgerymentioning
confidence: 99%